Characteristics of circulating CD31+ cells from patients with coronary artery disease. Issue 11 (30th September 2014) - Kim, Moo Hyun; Guo, Longzhe; Kim, Han‐Soo; Kim, Sung‐Whan
Abstract Recently, we reported the properties of CD31‐expressing cells in healthy individuals. However, the characteristics of CD31‐expressing cells derived from coronary artery disease (CAD) patients remain unknown. This study aimed to investigate the relationship between circulating CD31+ cells and CAD as well as their biological characteristics. Analysis with flow cytometry revealed that CD31+ cells (C‐CD31) from the peripheral blood (PB) of CAD patients exhibited low levels of T‐cell marker and high levels of macrophage marker compared with the PB‐CD31+ cells from healthy individuals (H‐CD31). In addition, the expression levels of multiple pro‐angiogenic and chemokine genes were significantly down‐regulated in C‐CD31. However, inflammatory gene IL‐1α was highly up‐regulated in C‐CD31. Patients with unstable angina (UA) had significantly more CD31+ cells in the PB than healthy control group (P < 0.001). Moreover, there were significant correlations between the number of CD31+ cells and cardiovascular (CV) disease activity (R = 0.318, P = 0.006) and the number of diseased coronaries (R = 0.312, P = 0.005). For the diagnostic category of UA, the area under curve was 0.803 (P < 0.001). In conclusion, C‐CD31 have impaired angiogenic potential and the number of circulating CD31+ cells were correlated with CV risk. These findings may contribute to the understanding of the pathogenesis of CAD.